(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Fish oil, containing omega-3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoic acid, has attracted considerable interest for its health advantages, such as reducing inflammation and decreasing triglyceride levels. Nonetheless, fish oil is highly susceptible to oxidation, resulting in rancidity, reduced effectiveness, and unwanted smells, creating difficulties in its application as a dietary supplement. Using gelatin, encapsulation is commonly used to safeguard fish oil from oxidation and enhance its stability. This method involves enveloping the oil in a biopolymer to create a shield that guards against elements such as oxygen and light. Gelatin, obtained from different animal origins, is important in encapsulation. Various forms of gelatin, such as porcine skin gelatin (PSG), bovine skin gelatin (BSG), and fish gelatin (FG), have different characteristics that impact encapsulation efficiency and the stability of the enclosed fish oil. PSG and BSG are well-liked because they are readily accessible, cost-efficient, and have outstanding gel-forming capabilities. Nevertheless, their use may be restricted in specific markets due to dietary and religious guidelines. FG, obtained from fish skin and bones, is a better option that meets these limitations and fits well with human biology. A thorough search plan was created to locate pertinent papers from electronic databases such as PubMed, Google Scholar, Web of Science, or Scopus. This review examines the utilization of various kinds of gelatin to encapsulate fish oil, studying how their physical and chemical properties disturb the stability and efficacy of the encapsulated fish oil. The research also emphasizes the difficulties presented by oxidation and the significance of encapsulation in preserving the nutritional value and longevity of fish oil supplements. This review aims to offer insights into using different types of gelatins for encapsulating fish oil to enhance its oxidative stability and health advantages through a comparative analysis.